Paste vinyl chloride-based resin for synthetic leather
A paste vinyl chloride-vinyl acetate copolymer with specific vinyl acetate residue units and polymerization degree addresses flexibility and texture issues in synthetic leather, ensuring excellent mechanical strength and processability.
Patent Information
- Application Number
- JP2024058761
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-04-01
- Publication Date
- 2025-01-20
AI Technical Summary
Existing PVC resins for synthetic leather lack flexibility and texture, and the use of plasticizers can lead to stickiness and processability issues.
A paste vinyl chloride-vinyl acetate copolymer with specific vinyl acetate residue units (3 to 15% by weight) and an average degree of polymerization (900 to 2,200) is used to enhance flexibility and texture, while maintaining processability.
The copolymer provides synthetic leather with excellent flexibility, mechanical strength, and improved processability, avoiding stickiness and viscosity changes during processing.
Smart Images

Figure 2025009807000001 
Figure 2025009807000002 
Figure 2025009807000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a paste vinyl chloride resin having properties suitable for use in synthetic leather, and in particular to a paste vinyl chloride resin which has a specific amount of vinyl acetate residue units and an average degree of polymerization, thereby making it possible to provide synthetic leather with excellent flexibility and feel, and to synthetic leather containing the same. [Background technology]
[0002] Paste polyvinyl chloride resin (hereinafter sometimes abbreviated as paste PVC) is generally kneaded with a plasticizer, a filler, a stabilizer or other compounding agents to prepare a paste PVC sol, which is then used in a variety of molded products such as wallpaper, carpet tiles, gloves, etc., by a variety of molding methods.
[0003] Also, synthetic leather made of polyvinyl chloride resin, which has high mechanical strength and excellent resistance to abrasion, chemicals, and oil, has been proposed for use in a wide range of fields, including automobile interiors, furniture, bags and sacks, footwear, clothing, and stationery (see, for example, Patent Document 1). Although the flexibility of such synthetic leather can be improved by adding a plasticizer, there have been cases where, depending on the amount added, problems arise that affect the feel, such as stickiness caused by the plasticizer, in addition to imparting flexibility.
[0004] Therefore, a method using a specific plasticizer has been proposed (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-116875 [Patent Document 2] Japanese Patent Application Publication No. 6-2281 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the proposals in Patent Documents 1 and 2 only propose synthetic leather and its composition, and do not consider paste PVC resins for use in synthetic leather. Therefore, the effects of the study of plasticizers alone are limited.
[0007] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a paste PVC suitable for use in synthetic leather, which enables the provision of synthetic leather having excellent flexibility and feel, and a synthetic leather made therefrom. [Means for solving the problem]
[0008] As a result of intensive research into the above-mentioned problems, the present inventors have discovered that a paste vinyl chloride-vinyl acetate copolymer containing a specific amount of vinyl acetate residue units and having a specific average degree of polymerization is a paste PVC suitable for use in synthetic leather having excellent flexibility and feel, and have thus completed the present invention.
[0009] That is, the present invention relates to a paste PVC for synthetic leather, which is characterized by being a paste vinyl chloride-vinyl acetate copolymer containing 3 to 15 weight % of vinyl acetate residue units and having an average degree of polymerization of 900 to 2200, and to synthetic leather, which is characterized by containing the same.
[0010] The present invention will be described in detail below.
[0011] The paste vinyl chloride for synthetic leather of the present invention is a paste vinyl chloride-vinyl acetate copolymer containing 3-15% by weight of vinyl acetate residue units and having an average degree of polymerization of 900-2200. The paste vinyl chloride-vinyl acetate copolymer has a vinyl acetate residue unit content of 3-15% by weight (i.e., the vinyl acetate residue unit content is equivalent to 3-15 parts by weight relative to 100 parts by weight of vinyl chloride-vinyl acetate copolymer), and is preferably 7-12% by weight of the vinyl acetate residue unit (i.e., the vinyl acetate residue unit content is equivalent to 7-12 parts by weight relative to 100 parts by weight of vinyl chloride-vinyl acetate copolymer) since it exhibits excellent flexibility as a synthetic leather. Here, if the vinyl acetate residue unit content is less than 3% by weight, the synthetic leather will have poor flexibility. On the other hand, if the vinyl acetate residue unit content is more than 15% by weight, the viscosity of the paste vinyl chloride sol will change significantly over time when processed into synthetic leather, resulting in poor processability.
[0012] The vinyl chloride-vinyl acetate copolymer paste has an average degree of polymerization of 900 to 2200, and since it is possible to provide a particularly excellent synthetic leather, it is preferable that the average degree of polymerization is 1000 to 2000. If the average degree of polymerization is less than 900, the mechanical strength of the synthetic leather produced will be poor. On the other hand, if the average degree of polymerization is more than 2200, the processability of the synthetic leather produced will be poor. The average degree of polymerization can be determined, for example, by a method in accordance with JIS-K6721.
[0013] The vinyl chloride paste for synthetic leather of the present invention is preferably a vinyl chloride-vinyl acetate copolymer that has a continuous distribution of vinyl acetate residue unit content with one maximum value and a mode value of 1 to 30% by weight, since the change in viscosity over time when the vinyl chloride paste is made into a vinyl chloride sol is small and the synthetic leather has excellent mechanical strength. In this case, the vinyl acetate residue unit content distribution can be measured by, for example, measuring the concentration of a component separated into vinyl acetate residue units by 2D-HPLC or gradient elution method of liquid chromatography using an evaporative light scattering detector to obtain the distribution of vinyl acetate residue unit content. Note that the continuous distribution in which the mode value of the vinyl acetate residue unit content is within the range of 1 to 30% by weight and the distribution has one maximum value indicates the composition distribution of vinyl acetate residue units in the vinyl acetate-vinyl chloride copolymer, and further the uniformity of the composition distribution. The narrower the distribution range of the vinyl acetate residue unit content, the smaller the number of maximum values, and the stronger the strength, the more uniform the vinyl acetate residue unit content.
[0014] The paste PVC for synthetic leather of the present invention is a paste PVC and is therefore composed of aggregates of primary particles of vinyl chloride-vinyl acetate copolymer. The primary particle diameter of the paste PVC sol is preferably 0.1 to 5 μm, showing the maximum peak of the cumulative weight frequency, in order to reduce the change in viscosity over time when made into a paste PVC sol and to provide a paste PVC suitable for synthetic leather having excellent processability, and is particularly preferably 0.5 to 3.0 μm, and more preferably 1.0 to 2.0 μm.
[0015] The paste vinyl chloride-vinyl acetate copolymer constituting the paste PVC for synthetic leather of the present invention may be any one generally known as a vinyl chloride-vinyl acetate copolymer suitable for paste processing, for example, any one of paste vinyl chloride-vinyl acetate copolymers obtained by polymerizing vinyl chloride monomer and vinyl acetate monomer by emulsion polymerization method, microsuspension polymerization method, seed emulsion polymerization method, seed microsuspension polymerization method, etc. Also, it may be a commercially available product.
[0016] The PVC paste for synthetic leather of the present invention makes it possible to provide synthetic leather excellent in flexibility and touch, and such synthetic leather can be, for example, synthetic leather consisting of at least a skin layer, a foam layer, and a base fabric, and among them, a laminated structure having a base fabric as a substrate, a foam layer in the middle, and a skin layer on the outer surface is preferable because it results in synthetic leather excellent in touch and design. The PVC paste for synthetic leather of the present invention can be used as a constituent material for the skin layer and / or the foam layer.
[0017] When the PVC paste for synthetic leather of the present invention is used for a surface layer, it is preferable to contain 40 to 100 parts by weight of a plasticizer per 100 parts by weight of vinyl chloride-vinyl acetate copolymer, particularly 50 to 90 parts by weight, and further preferably 50 to 80 parts by weight, since the paste has excellent flexibility and does not cause quality and hygiene problems such as bleed-out. The plasticizer used in this case may be any plasticizer generally known for use in vinyl chloride resins, and among these, at least one plasticizer selected from the group consisting of diisononyl phthalate, bis(2-ethylhexyl) terephthalate, diisodecyl phthalate, dibutyl phthalate, (2-ethylhexyl) adipate, diisononyl adipate, tri(2-ethylhexyl) trimellitate, and triisodecyl trimellitate is preferred, as this will result in synthetic leather with an excellent balance between flexibility, permanent elongation, and mechanical strength, and diisononyl phthalate (hereinafter sometimes referred to as DINP) is preferred, as this will result in synthetic leather with extremely excellent flexibility.
[0018] When forming the surface layer, other pigments, diluents, inorganic fillers, heat stabilizers, viscosity regulators, colorants, flame retardants, etc. can be added. As the inorganic filler, any of calcium carbonates such as precipitated calcium carbonate, heavy calcium carbonate, and ultrafine calcium carbonate, magnesium carbonate, silicates such as silica, talc, diatomaceous earth, clay, and mica, aluminum hydroxide, and alumina can be used. Examples of the heat stabilizer include metal soaps such as magnesium stearate, aluminum stearate, calcium stearate, barium stearate, zinc stearate, calcium laurate, barium laurate, and zinc laurate, metal salts of phenol and naphthol such as sodium, zinc, and barium, organic tin compounds such as dibutyltin dilaurate and dibutyltin dimaleate, and phosphorous esters such as diethyl phosphite, dibutyl phosphite, dioctyl phosphite, diphenyl isodecyl phosphite, tricresyl phosphite, triphenyl phosphite, tris(nonylphenyl)phosphite, and triisooctyl phosphite. Examples of the viscosity regulator and diluent include solvents such as xylene, solvent naphtha, mineral spirits, diisobutyl ketone, and butyl acetate, and suitable surfactants, and examples of the flame retardant include antimony trioxide, red phosphorus, zinc borate, organic bromides, and chlorinated paraffins.
[0019] In order to further enhance the design and texture of the surface layer, the surface layer may be provided with various patterns, such as a lattice pattern, a check pattern, a grain pattern, a diamond pattern, a heart pattern, a clover pattern, a spade pattern, a cow pattern, a lizard pattern, a snake pattern, a crocodile pattern, a tiger pattern, a leopard pattern, etc., and may further be surface-treated with enamel, glitter, a gloss agent, etc.
[0020] When the PVC paste for synthetic leather of the present invention is used for a foam layer, it is preferable that the paste contains 50 to 150 parts by weight of a plasticizer, more preferably 70 to 130 parts by weight, and further preferably 90 to 110 parts by weight, per 100 parts by weight of vinyl chloride-vinyl acetate copolymer, since it is particularly excellent in flexibility and does not cause quality or hygienic problems such as bleed-out. In this case, the plasticizer may be the same as those mentioned above.
[0021] In addition, when forming a foamed layer, it is preferable to use 2 to 7 parts by weight of a foaming agent relative to 100 parts by weight of the vinyl chloride-vinyl acetate copolymer paste, particularly 3 to 6 parts by weight, and more preferably 4 to 6 parts by weight. The foaming agent may be one generally known as a foaming agent for vinyl chloride resins, such as azodicarbonamide, azobisisobutyronitrile, benzenesulfonyl hydrazide, p-toluenesulfonyl hydrazide, p,p'-oxybis(benzenesulfonyl hydrazide), dinitrosopentanemethylenetetramine, N,N'-dinitroso-N,N'-dimethylterephthalamide, trihydrazinotriamine, etc. These foaming agents may be used alone or in combination of two or more.
[0022] When forming the foamed layer, the above-mentioned other pigments, diluents, inorganic fillers, heat stabilizers, viscosity regulators, colorants, flame retardants, etc. may be further blended.
[0023] The foam layer may be either a closed cell foam layer or an open cell foam layer, and among them, a closed cell foam layer with uniform cells is preferable because it provides synthetic leather with an excellent balance between touch and durability. The foam layer preferably has an expansion ratio of 2 to 10 times, and more preferably 3 to 7 times.
[0024] The base fabric (sometimes called fabric) supports the foam layer and further the skin layer, and any fabric (base fabric) used for general synthetic leather or artificial leather can be used, including knitted fabric, woven fabric, nonwoven fabric, etc. Examples of knitted fabric, woven fabric, nonwoven fabric, etc. include those made of a single fiber selected from synthetic fibers such as polyester, polyamide, polyacrylonitrile, nylon, etc., natural fibers such as cotton, hemp, etc., regenerated fibers such as rayon, acetate, etc., or blends of these fibers.
[0025] The method for producing the synthetic leather of the present invention may be any method which allows production of synthetic leather consisting of at least a surface layer, a foam layer and a base fabric, and examples of such methods include a method in which the surface layer, the foam layer and the base fabric are bonded together by adhesive, thermocompression or the like, a method in which a paste vinyl chloride sol for the surface layer and a paste vinyl chloride sol for the foam layer are prepared and laminated together, and then the base fabric is laminated and heated to effect resinification and foaming, and the like.
[0026] When preparing the paste vinyl chloride sol for the skin layer and the paste vinyl chloride sol for the foam layer, examples of the method include a method of uniformly mixing the paste vinyl chloride, the plasticizer, and further, if necessary, the foaming agent and other additives, using, for example, a planetary mixer, a kneader, a three-roll machine, a Hobart mixer, a butterfly mixer, a dissolver, a Raikai machine, a ribbon blender, a Henschel mixer, etc. When shaping, examples of the method include a method of spreading the mixture on a release paper using, for example, a doctor knife, a reverse roll, a natural roll, a floating knife, an air knife, a curtain flow, or spraying the mixture with a spray.
[0027] The synthetic leather of the present invention has excellent flexibility and feel, and can be used in a wide range of fields, including automobile interiors such as seats, dashboards, instrument panels, door panels, roof panels, and console boxes, as well as furniture such as sofas, chests of drawers, and cupboards, bags and pouches such as business bags, pouches, and handbags, footwear such as shoes and sandals, clothing such as jackets, coats, and jumpers, and stationery. Effect of the Invention
[0028] The synthetic leather containing the paste PVC of the present invention has excellent flexibility and feel, and is therefore expected to be used in a wide range of fields, including automobile interiors, furniture, bags, footwear, clothing, stationery, etc. EXAMPLES
[0029] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0030] The evaluation and measurement methods in the examples are shown below.
[0031] <Flexibility assessment> The flexibility of the synthetic leathers obtained in the Examples and Comparative Examples was evaluated based on the feel to the touch by a number of randomly selected persons. ○: The synthetic leather felt soft to the touch. ×: The synthetic leather felt hard when gripped.
[0032] <Average degree of polymerization> The calculation was based on JIS-K6721.
[0033] <Average vinyl acetate residue unit content> The average vinyl acetate residue unit content (wt%) (sometimes referred to as VAc content) contained in the vinyl chloride-vinyl acetate paste copolymer was calculated from the spectrum of a measurement sample obtained by mixing 100 mg of vinyl chloride-vinyl acetate paste copolymer particles with 10 mg of potassium bromide, grinding and molding the mixture with an infrared spectrophotometer (manufactured by Shimadzu Corporation, (product name) FTIR-8100A) using the following formula: VAc content=(3.73×B / A+0.024)×1.04 A: 1430cm -1 Abs. value of the absorption peak top due to CH in-plane bending angle in the vicinity. B:1740cm -1 Abs. value of the absorption peak top due to C=O stretching near
[0034] Synthesis Example 1 1m 3 360 kg of deionized water, 300 kg of vinyl chloride monomer, 5.7 kg of lauroyl peroxide, and 30 kg of 15 wt% aqueous sodium dodecylbenzenesulfonate solution were charged into a stainless steel autoclave, and the mixture was circulated for 3 hours using a homogenizer to perform homogenization, after which the temperature of the reaction system was raised to 45°C to initiate polymerization. After the pressure of the polymerization system was reduced, the unreacted vinyl chloride monomer was recovered, and a vinyl chloride resin seed latex (a) was obtained that had a solid content of 35 wt%, an average particle size of 0.55 μm, and contained 2 wt% of lauroyl peroxide relative to the vinyl chloride resin.
[0035] Synthesis Example 2 1m 3 A stainless steel autoclave was charged with 400 kg of deionized water, 300 kg of vinyl chloride monomer, 81 g of potassium persulfate, and 10 kg of 16 wt% aqueous potassium laurate solution, and the temperature of the reaction system was raised to 54°C to initiate polymerization. From the start of polymerization to the end of polymerization, 0.7 parts by weight of an aqueous 15 wt% sodium dodecylbenzenesulfonate solution relative to the vinyl chloride monomer was continuously added. After the pressure of the polymerization system was reduced, the unreacted vinyl chloride monomer was recovered, and a vinyl chloride resin seed latex (b) with a solid content of 40 wt% and an average particle size of 0.15 μm was obtained.
[0036] Example 1 In a 2.5-liter autoclave, 610 g of deionized water, 493 g of vinyl chloride monomer (62% by weight based on the total amount of mixed monomers) and 96 g of vinyl acetate monomer (12% by weight based on the total amount of mixed monomers) as first-stage monomers, 9 g of 5% aqueous sodium lauryl sulfate, 85 g of seed latex (a) with an average particle size of 0.55 μm obtained in Synthesis Example 1, and 4 g of 0.1% aqueous copper sulfate were charged, and then the temperature of the reaction mixture was raised to 35° C. to start the first-stage polymerization, and a 0.05% by weight aqueous ascorbic acid solution was continuously added throughout the entire polymerization time so as to maintain the polymerization temperature. When the polymerization conversion rate reached 50%, 140 g of vinyl chloride monomer (17% by weight based on the total amount of mixed monomers) was charged as the second-stage monomer into the 2.5-liter autoclave, and the second-stage polymerization was continued at a polymerization temperature of 35° C.
[0037] Furthermore, when the polymerization conversion rate based on the total amount of the first-stage and second-stage charged monomers reached 80%, 70 g of vinyl chloride monomer (9% by weight based on the total amount of the mixed monomers charged) was charged into a 2.5-liter autoclave as the third-stage charged monomer, and the third-stage polymerization was continued at a polymerization temperature of 35° C., and the polymerization was terminated when the polymerization conversion rate based on the total amount of the mixed monomers reached 90%.
[0038] From the start of polymerization to the end of polymerization, 0.7 parts by weight of a 5% by weight aqueous solution of sodium lauryl sulfate and 0.1 parts by weight of an aqueous solution of a nonylpropenylphenol ethylene oxide 10 mol adduct sulfate ester ammonium salt (manufactured by Daiichi Kogyo Seiyaku: (trade name) AQUALON BC-1025) were continuously added relative to the vinyl chloride monomer to obtain a vinyl chloride-vinyl acetate copolymer latex.
[0039] 1 kg of the obtained vinyl chloride-vinyl acetate copolymer latex was spray-dried using a rotary disk type spray dryer at a hot air temperature of 160°C and an outlet temperature of 60°C to obtain a paste vinyl chloride-vinyl acetate copolymer, paste PVC for synthetic leather. The content of vinyl acetate residue units in the obtained paste PVC for synthetic leather was 9.0wt% and the degree of polymerization was 1900.
[0040] Example 2 In a 2.5-liter autoclave, 610 g of deionized water, 501 g of vinyl chloride monomer (62% by weight based on the total amount of mixed monomers) and 82 g of vinyl acetate monomer (10% by weight based on the total amount of mixed monomers) as first-stage monomers, 9 g of 5% aqueous sodium lauryl sulfate, 85 g of seed latex (a) with an average particle size of 0.55 μm obtained in Synthesis Example 1, and 4 g of 0.1% aqueous copper sulfate were charged, and then the temperature of the reaction mixture was raised to 40° C. to start the first-stage polymerization, and a 0.05% by weight aqueous ascorbic acid solution was continuously added throughout the entire polymerization time so as to maintain the polymerization temperature. When the polymerization conversion rate reached 73%, 140 g of vinyl chloride monomer (17% by weight based on the total amount of mixed monomers) was charged as the second-stage monomer into the 2.5-liter autoclave, and the second-stage polymerization was continued at a polymerization temperature of 35° C.
[0041] Furthermore, when the polymerization conversion rate based on the total amount of the first-stage and second-stage charged monomers reached 82%, 70 g of vinyl chloride monomer (9% by weight based on the total amount of the mixed monomers charged) was charged into a 2.5-liter autoclave as the third-stage charged monomer, and the third-stage polymerization was continued at a polymerization temperature of 35° C., and the polymerization was terminated when the polymerization conversion rate based on the total amount of the mixed monomers reached 90%.
[0042] From the start of polymerization to the end of polymerization, 0.7 parts by weight of a 5% by weight aqueous solution of sodium lauryl sulfate and 0.1 parts by weight of an aqueous solution of a nonylpropenylphenol ethylene oxide 10 mol adduct sulfate ester ammonium salt (manufactured by Daiichi Kogyo Seiyaku: (trade name) AQUALON BC-1025) were continuously added relative to the vinyl chloride monomer to obtain a vinyl chloride-vinyl acetate copolymer latex.
[0043] 1 kg of the obtained vinyl chloride-vinyl acetate copolymer latex was spray-dried using a rotating disk type spray dryer at a hot air temperature of 160°C and an outlet temperature of 60°C to obtain a paste vinyl chloride-vinyl acetate copolymer, paste PVC for synthetic leather. The content of vinyl acetate residue units in the obtained paste PVC for synthetic leather was 6.6wt%, and the degree of polymerization was 1810.
[0044] Example 3 In a 2.5-liter autoclave, 610 g of deionized water, 225 g of vinyl chloride monomer (26% by weight based on the total amount of mixed monomers) and 51 g of vinyl acetate monomer (6% by weight based on the total amount of mixed monomers) as first-stage monomers, 9 g of 5% aqueous sodium dodecylbenzenesulfonate, 90 g of seed latex (a) with an average particle size of 0.55 μm obtained in Synthesis Example 1, and 4 g of 0.1% aqueous copper sulfate were charged, and then the temperature of the reaction mixture was raised to 47° C. to start the first-stage polymerization, and a 0.05% by weight aqueous ascorbic acid solution was continuously added throughout the entire polymerization time so as to maintain the polymerization temperature. When the polymerization conversion rate reached 85%, 250 g of vinyl chloride monomer (29% by weight based on the total amount of mixed monomers) was charged as the second-stage monomer into the 2.5-liter autoclave, and the second-stage polymerization was continued at a polymerization temperature of 44° C.
[0045] Furthermore, when the polymerization conversion rate based on the total of the first-stage and second-stage charged monomers reached 89%, 331 g of vinyl chloride monomer (39% by weight based on the total charged amount of mixed monomers) was charged as the third-stage charged monomer into the 2.5-liter autoclave, and the third-stage polymerization was continued at a polymerization temperature of 40° C., and the polymerization was terminated when the polymerization conversion rate based on the total of the mixed monomers reached 90%.
[0046] From the start of polymerization to the end of polymerization, 0.7 parts by weight of a 5% by weight aqueous solution of sodium dodecylbenzenesulfonate relative to the vinyl chloride monomer was continuously added to obtain a vinyl chloride-vinyl acetate copolymer latex.
[0047] 1 kg of the obtained vinyl chloride-vinyl acetate copolymer latex was spray-dried using a rotating disk type spray dryer at a hot air temperature of 160°C and an outlet temperature of 60°C to obtain a paste vinyl chloride-vinyl acetate copolymer, paste PVC for synthetic leather. The content of vinyl acetate residue units in the obtained paste PVC for synthetic leather was 4.8wt%, and the degree of polymerization was 1650.
[0048] Example 4 In a 2.5-liter autoclave, 610 g of deionized water, 227 g of vinyl chloride monomer (28% by weight based on the total amount of mixed monomers) and 41 g of vinyl acetate monomer (5% by weight based on the total amount of mixed monomers) as first-stage monomers, 9 g of 5% aqueous sodium dodecylbenzenesulfonate, 90 g of seed latex (a) with an average particle size of 0.55 μm obtained in Synthesis Example 1, and 4 g of 0.1% aqueous copper sulfate were charged, and then the temperature of the reaction mixture was raised to 58° C. to start the first-stage polymerization, and a 0.05% by weight aqueous ascorbic acid solution was continuously added throughout the entire polymerization time so as to maintain the polymerization temperature. When the polymerization conversion rate reached 86%, 227 g of vinyl chloride monomer (28% by weight based on the total amount of mixed monomers) was charged as the second-stage monomer into the 2.5-liter autoclave, and the second-stage polymerization was continued at a polymerization temperature of 55° C.
[0049] Furthermore, when the polymerization conversion rate based on the total amount of the first-stage and second-stage charged monomers reached 90%, 300 g of vinyl chloride monomer (38% by weight based on the total amount of the mixed monomers charged) was charged as the third-stage charged monomer into a 2.5-liter autoclave, and the third-stage polymerization was continued at a polymerization temperature of 51° C., and the polymerization was terminated when the polymerization conversion rate based on the total amount of the mixed monomers reached 90%.
[0050] From the start of polymerization to the end of polymerization, 0.7 parts by weight of a 5% by weight aqueous solution of sodium dodecylbenzenesulfonate relative to the vinyl chloride monomer was continuously added to obtain a vinyl chloride-vinyl acetate copolymer latex.
[0051] 1 kg of the obtained vinyl chloride-vinyl acetate copolymer latex was spray-dried using a rotating disk type spray dryer at a hot air temperature of 115°C and an outlet temperature of 55°C to obtain a paste vinyl chloride-vinyl acetate copolymer, paste PVC for synthetic leather. The content of vinyl acetate residue units in the obtained paste PVC for synthetic leather was 4.0wt% and the degree of polymerization was 1020.
[0052] Synthesis Example 3 In a 2.5-liter autoclave, 610 g of deionized water, 420 g of vinyl chloride monomer as a first-stage monomer charge (60% by weight relative to the total amount of the mixed monomer charge), 8 g of 5% aqueous sodium lauryl sulfate, 85 g of seed latex (a) with an average particle size of 0.55 μm obtained in Synthesis Example 1, and 4 g of 0.1% aqueous copper sulfate were charged, and then the temperature of this reaction mixture was raised to 49° C. to start the first-stage polymerization, and a 0.05% by weight aqueous ascorbic acid solution was continuously added throughout the entire polymerization time so as to maintain the polymerization temperature. When the polymerization conversion rate reached 88%, 280 g of vinyl chloride monomer as a second-stage monomer charge (40% by weight relative to the total amount of the mixed monomer charge) was charged into the 2.5-liter autoclave, and the second-stage polymerization was continued at a polymerization temperature of 45° C., and the polymerization was terminated when the polymerization conversion rate relative to the total amount of the mixed monomer reached 90%.
[0053] From the start of polymerization to the end of polymerization, 0.7 parts by weight of a 5% by weight aqueous solution of sodium lauryl sulfate relative to the vinyl chloride monomer was continuously added to obtain a vinyl chloride polymer latex.
[0054] 1 kg of the obtained vinyl chloride polymer latex was spray-dried using a rotating disk type spray dryer at a hot air temperature of 160° C. and an outlet temperature of 60° C. to obtain a vinyl chloride polymer paste. The degree of polymerization of the obtained vinyl chloride polymer paste was 1660.
[0055] Synthesis Example 4 In a 2.5L stainless steel autoclave, 610g of deionized water, 800g of vinyl chloride monomer, 10g of 5% by weight sodium sulfosuccinate aqueous solution, 4 parts by weight of seed latex (a) having an average particle size of 0.55 μm obtained in Synthesis Example 1 relative to 100 parts by weight of vinyl chloride monomer, and 1 part by weight of seed latex (b) having an average particle size of 0.15 μm obtained in Synthesis Example 2 relative to 100 parts by weight of vinyl chloride monomer were charged, and the temperature of this reaction mixture was raised to 42°C to initiate polymerization. From the start of polymerization to the end of polymerization, 0.5 parts by weight of 5% by weight sodium sulfosuccinate aqueous solution relative to vinyl chloride monomer was continuously added. When the polymerization pressure dropped from the saturated vapor pressure of vinyl chloride monomer at 42°C to 0.30 MPa, the polymerization was stopped, and unreacted vinyl chloride monomer was recovered to obtain a vinyl chloride polymer latex.
[0056] 1 kg of the obtained vinyl chloride polymer latex was spray-dried using a rotating disk type spray dryer at a hot air temperature of 160° C. and an outlet temperature of 60° C. to obtain a vinyl chloride polymer paste. The degree of polymerization of the obtained vinyl chloride polymer paste was 2120.
[0057] Synthesis Example 5 In a 2.5L stainless steel autoclave, 610g of deionized water, 730g of vinyl chloride monomer, 15g of 5% by weight sodium dodecylbenzenesulfonate aqueous solution, 4 parts by weight of seed latex (a) having an average particle size of 0.55μm obtained in Synthesis Example 1 relative to 100 parts by weight of vinyl chloride monomer, and 5 parts by weight of seed latex (b) having an average particle size of 0.15μm obtained in Synthesis Example 2 relative to 100 parts by weight of vinyl chloride monomer were charged, and the temperature of this reaction mixture was raised to 54°C to initiate polymerization. From the start of polymerization to the end of polymerization, 0.7 parts by weight of a 5% by weight sodium lauryl sulfate aqueous solution relative to the vinyl chloride monomer was continuously added. When the polymerization pressure dropped from the saturated vapor pressure of the vinyl chloride monomer at 54°C to 0.35MPa, the polymerization was stopped, and unreacted vinyl chloride monomer was recovered to obtain a vinyl chloride polymer latex.
[0058] 1 kg of the obtained vinyl chloride polymer latex was spray-dried using a rotary disk type spray dryer at a hot air temperature of 160°C and an outlet temperature of 60°C to obtain a vinyl chloride polymer paste. The obtained vinyl chloride polymer paste did not contain sodium lauryl sulfate or nonylpropenylphenol ethylene oxide 10 mol adduct sulfate ammonium salt. The degree of polymerization was 1120.
[0059] Example 5 To 100 parts by weight of the paste PVC for synthetic leather obtained in Example 1, 60 parts by weight of DINP (manufactured by J-Plus) as a plasticizer and 3 parts by weight of a calcium-zinc composite heat stabilizer (manufactured by ADEKA, (grade name) SC-320) were added and kneaded using a dissolver to prepare a paste PVC sol for the surface layer.
[0060] To 100 parts by weight of the paste PVC obtained in Synthesis Example 5, 100 parts by weight of DINP (manufactured by J-Plus Co., Ltd.) as a plasticizer, 50 parts by weight of calcium carbonate ((product name) NN#500, manufactured by Nitto Funka Kogyo Co., Ltd.), 4 parts by weight of titanium oxide (Teika Co., Ltd., product name JR600A) as a pigment, 5 parts by weight of a foaming agent (Otsuka Chemical Co., Ltd., product name AZ Ultra 1050), and 1.6 parts by weight of a stabilizer (Asahi Denka Co., Ltd., product name FL103N) were added and kneaded using a dissolver to prepare a paste PVC sol for a foam layer.
[0061] Then, a release paper that had been heated in advance at 180°C for 5 seconds was coated with a paste vinyl chloride sol for the surface to a thickness of 0.2 mm, and heated at 180°C for 10 seconds to obtain raw fabric 1. After that, a paste vinyl chloride sol for the foam layer was coated on raw fabric 1 to a thickness of 0.2 mm, and heated at 200°C for 6 seconds to obtain raw fabric 2. A knitted fabric was then attached to the foam layer surface as a base fabric, and heated at 200°C for 90 seconds to gel (resinify) and foam, and the release paper was peeled off to obtain a synthetic leather having a closed-cell foam layer as the foam layer.
[0062] The evaluation results of the obtained synthetic leather are shown in Table 1. The obtained synthetic leather was flexible and had an excellent feel.
[0063] Examples 6 to 8 Synthetic leathers having a closed-cell foam layer as a foam layer were obtained in the same manner as in Example 1, except that the paste PVC for synthetic leathers obtained in Examples 2, 3 and 4 were used as the paste PVC sol for the surface layer instead of the paste PVC for synthetic leather obtained in Example 1, and the synthetic leathers having the closed-cell foam layer as a foam layer were evaluated.
[0064] The evaluation results are shown in Table 1. The resulting synthetic leather was flexible and had an excellent feel.
[0065] Example 9 A synthetic leather having a closed-cell foam layer as a foam layer was obtained in the same manner as in Example 1, except that the paste PVC for synthetic leather obtained in Example 1 was used as the paste PVC sol for the foam layer instead of the paste PVC obtained in Synthesis Example 5, and the synthetic leather was evaluated.
[0066] Example 10 An artificial leather was obtained in the same manner as in Example 1, except that the amount of plasticizer in the vinyl chloride paste for the skin layer was changed to 80 parts, and the synthetic leather was evaluated.
[0067] Example 11 An artificial leather was obtained in the same manner as in Example 1, except that the amount of plasticizer in the vinyl chloride paste for the foam layer was changed to 120 parts, and the synthetic leather was evaluated.
[0068] [Table 1]
[0069] Comparative Examples 1-2 Synthetic leather was obtained in the same manner as in Example 1, except that the paste vinyl chloride polymer obtained in Synthesis Examples 3 and 4 was used as the sol for the surface layer instead of the paste vinyl chloride for synthetic leather obtained in Example 1, and the synthetic leather was evaluated.
[0070] The evaluation results are shown in Table 2. The synthetic leather obtained had poor flexibility and a poor feel to the touch.
[0071] Comparative Example 3 Synthetic leather was obtained in the same manner as in Example 1, except that the paste vinyl chloride polymer obtained in Synthesis Example 3 was used for the sol for the surface layer instead of the paste vinyl chloride for synthetic leather obtained in Example 1, and the amount of plasticizer in the sol for the surface layer was changed to 80 parts by weight, and then the synthetic leather was evaluated.
[0072] The evaluation results are shown in Table 2. The synthetic leather obtained had poor flexibility and a poor feel to the touch.
[0073] Comparative Example 4 Synthetic leather was obtained in the same manner as in Example 1, except that the paste vinyl chloride polymer obtained in Synthesis Example 3 was used for the sol for the surface layer instead of the paste vinyl chloride for synthetic leather obtained in Example 1, the amount of plasticizer in the sol for the surface layer was changed to 80 parts by weight, and the amount of plasticizer in the sol for the foam layer was changed to 120 parts by weight, and then the synthetic leather was evaluated.
[0074] The evaluation results are shown in Table 2. The synthetic leather obtained had poor flexibility and a poor feel to the touch.
[0075] [Table 2]
[0076] The methods for measuring the distribution of vinyl acetate residue unit content and particle size distribution of the paste PVC for synthetic leather obtained in Examples 1 to 4 and Synthesis Example 5, and the paste PVC, are shown below. The results are shown in Table 3.
[0077] <Measurement of distribution of vinyl acetate residue unit content> The distribution of vinyl acetate residue unit content was measured by 2D-HPLC (two-dimensional HPLC). Apparatus: Agilent 1290 Infinity II series (Agilent Technologies). Detector: Evaporative light scattering detector (ELSD) G4260B (Agilent Technologies). 1st dimension (GPEC) Column: TSKgel ODS-80Ts (manufactured by Tosoh Corporation). Column temperature: 40°C. Mobile phase: Solution A: 50% MeOH aqueous solution Solution B: Tetrahydrofuran Flow rate: 0.6ml / min. Concentration: 1.0mg / ml. Injection volume: 20μl. 2nd dimension (GPC) Column: TSKgel SuperAWM-H (manufactured by Tosoh Corporation). Column temperature: 40°C. Eluent: Tetrahydrofuran Flow rate: 0.6ml / min. Loop volume: 40 μl.
[0078] <Particle size distribution> The synthetic leather paste PVC was dispersed in water, ultrasonically dispersed, and the particle size distribution was measured using a disk centrifugal particle size distribution measuring device (Nihon Luft Co., Ltd., (product name) DC24000UHR).
[0079] [Table 3] [Industrial Applicability]
[0080] The PVC paste for synthetic leather of the present invention can provide synthetic leather having excellent flexibility and touch, and the synthetic leather can be used in various industrial processes, and its industrial value is extremely high.
Claims
1. A paste vinyl chloride resin for synthetic leather, which is a paste vinyl chloride-vinyl acetate copolymer containing 3-15% by weight of vinyl acetate residue units and having an average degree of polymerization of 900-2200.
2. The vinyl chloride resin paste for synthetic leather according to claim 1, characterized in that the distribution of the vinyl acetate residue unit content shows a continuous distribution with one maximum value and a mode value of 1 to 30% by weight, and the particle size showing the maximum peak of the cumulative weight frequency in the primary particle size is 0.1 to 5 μm.
3. The synthetic leather is characterized by comprising a paste vinyl chloride-vinyl acetate copolymer having 3-15% by weight of vinyl acetate residue units and an average degree of polymerization of 900-2200.
4. The synthetic leather according to claim 3, which is composed of at least a surface layer, a foam layer, and a base fabric, and the surface layer and / or the foam layer contains a paste vinyl chloride-vinyl acetate copolymer having 3 to 15% by weight of vinyl acetate residue units and an average degree of polymerization of 900 to 2200.
5. 5. The synthetic leather according to claim 4, wherein the surface layer contains 40 to 100 parts by weight of a plasticizer for 100 parts by weight of a paste vinyl chloride-vinyl acetate copolymer having 3 to 15% by weight of vinyl acetate residue units and an average degree of polymerization of 900 to 2200.
6. 5. The synthetic leather according to claim 4, wherein the foam layer is a foam layer containing 50 to 150 parts by weight of a plasticizer for 100 parts by weight of a paste vinyl chloride-vinyl acetate copolymer having 3 to 15% by weight of vinyl acetate residue units and an average degree of polymerization of 900 to 2200.
7. 7. The synthetic leather according to claim 5, wherein the plasticizer is at least one selected from the group consisting of diisononyl phthalate, bis(2-ethylhexyl) terephthalate, diisodecyl phthalate, dibutyl phthalate, (2-ethylhexyl) adipate, diisononyl adipate, tri(2-ethylhexyl) trimellitate, and triisodecyl trimellitate.
8. A method for producing synthetic leather comprising laminating a surface layer, a foam layer and a base fabric, the method being characterized in that the surface layer and the foam layer are formed by paste processing, and the paste vinyl chloride sol for the surface layer and / or the paste vinyl chloride sol for the foam layer contains a paste vinyl chloride-vinyl acetate copolymer having 3-15% by weight of vinyl acetate residue units and an average degree of polymerization of 900-2200, and a plasticizer.
Citation Information
Patent Citations
Vinyl chloride resin leather for furniture
JP1994002281A
Pvc leather cloth
JP1994116875A